Arthur tricks the tooth fairy - Brown, Marc Tolon (New York : Random House, 1998)
Jealous when Arthur loses a tooth and receives a dollar for it, his sister tries to trick the Tooth Fairy into also visiting her.
"Step into Reading Books."
150
Accelerated Reader AR
Keywords: Tooth Fairy -- Fiction; Teeth -- Fiction; Animals -- Fiction; Brothers and sisters -- Fiction